Human-centered Reliability Assessment and Condition Monitoring in Road Transportation Systems - Khashayar, Hojjati Emami (Université d'Ottawa / University of Ottawa, 2015)
The risk analysis process involving information acquisition, modeling, analysis, and decision steps result in system design improvement. To allow an accurate and active system risk assessment in road transportation, this study identifies the contributing factors in reliability of road transportation systems and develops the systematic and stochastic methodologies and mathematical models. The developed models and methodologies aim to assess the reliability and risk of drivers interacting with the today’s typical vehicles equipped with Advanced Drivers Assistance System (ADAS) and Passive Safety Systems (PSS) with any degree of complexity and availability of such systems. The research further examines and addresses the specific needs of such vulnerable users and perhaps risk to others on roads including older drivers, younger drivers and pedestrians. The research presents the conditions monitoring concepts as in-vehicle tools for live assessment of risk state of drivers built on the methodologies and models developed in the studies. The necessity for availability of good data and specific databases for purpose of risk assessment in road transportation is then highlighted and stressed. The complete procedure for accident investigation and data collection is developed and presented in the research and a conceptual model for a typical human centered reliability databases in road transportation is also developed. The research is novel and innovative and expected to pave the way for improvement and development of new risk mitigating systems and better assessment and monitoring of the safety of users on roads and with the capability of information sharing resulting in saving many lives worldwide.
Keywords: Reliability; Road Transportation